2020
DOI: 10.1136/bmjopen-2020-038344
|View full text |Cite
|
Sign up to set email alerts
|

Benefits finding among Chinese family caregivers of stroke survivors: a qualitative descriptive study

Abstract: ObjectivesThe caregiving experience includes both caregiver burdens and benefits finding. However, the benefits obtained by family caregivers of stroke survivors in Chinese community dwellings are unknown. The objective of this study was to explore the benefits experienced by family caregivers of stroke survivors in Chinese community dwellings.DesignA qualitative descriptive design was used, fulfilling the consolidated criteria for the Standards for Reporting Qualitative Research reporting guidelines. Semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
1
23
1
1
Order By: Relevance
“…A qualitative study from China found that caregivers viewed their role as an obligation and expressive of love [ 39 ]. Another qualitative study on Chinese caregivers unveiled that caregiver was able to spend more time with the patients following a stroke event [ 40 ]. Moreover, caregivers became more reliable and sensible in the process [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study from China found that caregivers viewed their role as an obligation and expressive of love [ 39 ]. Another qualitative study on Chinese caregivers unveiled that caregiver was able to spend more time with the patients following a stroke event [ 40 ]. Moreover, caregivers became more reliable and sensible in the process [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another qualitative study on Chinese caregivers unveiled that caregiver was able to spend more time with the patients following a stroke event [ 40 ]. Moreover, caregivers became more reliable and sensible in the process [ 40 ]. These benefits acquired from having good patient-caregiver relationships may negate caregivers’ depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is praised in China, there is no government or community social service assistance, which leads to a greater burden on caregivers. 17,18 Health policy-makers' attention is increasingly directed toward the social challenges of caregiver burden and burnout. 19 It is essential for home medical care to include caregiver perspectives and needs as a standard component of its assessment and plan.…”
Section: O R I G I N a L R E S E A R C Hmentioning
confidence: 99%
“…indicated that Chinese American caregivers pay special attention to ‘filial piety’ originating from Confucian philosophy, which integrates ‘responsibility’ with caregiving from family members. Although it is praised in China, there is no government or community social service assistance, which leads to a greater burden on caregivers 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, others did not, hence highlighting differences in care that bring challenges in understanding care needs. However, it is important to note that the role of a caregiver is well documented [22,[37][38][39][40][41]. Further, by addressing the individual needs of stroke caregivers, it is possible to limit the feelings of fear, uncertainty, isolation, burnout, fatigue, etc.…”
Section: Comparison With Literaturementioning
confidence: 99%